2020
DOI: 10.1002/fsn3.1757
|View full text |Cite
|
Sign up to set email alerts
|

Consumers preferences on nutritional attributes of dairy‐alternative beverages: hedonic pricing models

Abstract: In the past decade, dairy alternative beverages have gained its market position as a robust competitor for conventional milk in the United States. Consumers have gradually turned away from conventional milk, leading the push towards plant-based milk products because a growing number of consumers beginning to believe that plant-based foods are healthier and more environmentally friendly than animal-based foods. As indicated by Singhal, Baker, and Baker (2017), the increasing sales trend of non-dairy beverages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…According to Kumar and Kapoor, when purchasing vegetarian food products, consumers considered three main types of attributes: credence attributes (e.g., nutritional value, freshness), search attributes (e.g., variety, size, and color), and experience attributes (e.g., taste, odor). Yang and Dharmasena (2020) found that when choosing a plant-based beverage, consumers commonly evaluate nutritional attributes such as calories, protein, fat, vitamin A and vitamin D, with protein being the most valued attribute. McCarthy et al (2017) likewise identified nutritional attributes to be important to consumers when choosing plant-based beverages, with sugar content in particular being an important attribute of consideration when making a purchase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Kumar and Kapoor, when purchasing vegetarian food products, consumers considered three main types of attributes: credence attributes (e.g., nutritional value, freshness), search attributes (e.g., variety, size, and color), and experience attributes (e.g., taste, odor). Yang and Dharmasena (2020) found that when choosing a plant-based beverage, consumers commonly evaluate nutritional attributes such as calories, protein, fat, vitamin A and vitamin D, with protein being the most valued attribute. McCarthy et al (2017) likewise identified nutritional attributes to be important to consumers when choosing plant-based beverages, with sugar content in particular being an important attribute of consideration when making a purchase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Almond, soy and coconut non-dairy beverages have been the recent market leaders, with the sales of oat-based beverages now experiencing a surge [ 2 ]. Preferences for the beverages vary depending upon a number of factors such as the flavor, price, packaging, taste, nutritional profile, and whether the product is organic, and free of genetically modified (GM) ingredients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The consumer’s perception of the product’s quality and the “healthy” characteristic are attributes increasingly demanded by consumers. In this sense, [ 33 ] indicated that consumers tend to pay premiums for nutritional attributes added to milk such as vitamins. [ 34 ] analyzed the Chinese market and the results found by this study showed that attributes of perception of nutritional content and green food have positive effects on food prices.…”
Section: Introductionmentioning
confidence: 99%